P119 Perianal Crohn's disease and the development of colorectal and anal cancer: A systematic review and meta-analysis. (30th January 2023) - Johansen, M P; ,
Abstract: Background: Over the course of their disease, 15-30% of patients with Crohn's disease(CD) develop Perianal Crohn's disease (pCD). In approximately 5% of patients, perianal fistula is the only manifestation of their CD. Previous studies have found that perianal involvement results in an 11-fold increased risk for anal cancer. The aim of this systematic review was to assess the literature on the incidence and risk factors for colorectal cancer and anal cancer in patients with perianal Crohn's disease. Methods: A systematic review of the literature was performed using PubMed, Embase and Google Scholar. A meta-analysis was then conducted using a random-effect model. Results: Five studies were included in the systematic review. Of the total patients, 26.5% had perianal Crohn's disease. The median follow-up was 6 years. In total, 127 cases of colorectal cancer were found [0.43% of the included Crohn's disease patients]. Perianal involvement was present in 50% of colorectal cancer patients [0.89% of the population]. Three of the studies specified the cancer to be rectal or anal, which were present in 68 and 24 cases [0.3% and 0.1% of patients], respectively. In a subgroup analysis of rectal and anal cancer, perianal involvement was most frequent in anal cancer, accounting for 46% of the cases. In the rectal cancer group, 37% had perianal involvement. The higher incidence of colorectal cancer in patients with perianal Crohn's disease was confirmed in a meta-analysis. Conclusion: Half of the patients with colorectal cancer and anal cancer were found to have perianal Crohn's disease. In patients with perianal involvement, there was a higher percentage of anal cancer compared with rectal cancer. These results support the theory that patients with perianal Crohn's disease are at increased risk for developing colorectal and anal cancer. Studies collecting more detailed data regarding patients and their cancers are needed to further specify the disease course.